Lithium-Associated Thyromegaly: An Unusual Cause of Airway Obstruction. (9th September 2012) - Verma, Ashish; Wartak, Siddharth; Tidswell, Mark
Abstract : Acute upper airway obstruction is a medical emergency and can be caused by many serious conditions such as a foreign body occluding the airway, intrinsic swelling (as in anaphylaxis), or extrinsic compression. Thyromegaly has rarely been reported as a source of airway compromise. We present a patient whose thyromegaly is presumed to have been induced by lithium and was massive enough to cause severe airway compromise.